Perancangan Penerapan Quick Response (QR) Kode Dalam Sistem Pendaftaran - Mochamad Sanwasih; Rachmat Setiabudi (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
The rapid development of technology and information systems has now been able to attract the attention of many organizations to support their activities, one of which is the development of an online registration system. There are problems that occur due to the unavailability or lack of use of the technology. Systems that are still manual processing can cause problems in the future. One of them is from problems that occur in poor data management, ambiguous participant data, the use of time used to be wasted and other obstacles. The application of the Quick Response (QR) code in the registration system is expected to help problems that occur so that data management becomes better and creates a more efficient and structured use of time. The system development of this registration system design uses the SDLC method and the model used is the waterfall model, which provides an overview from the analysis to the maintenance of the information system of the designed application. The system design to facilitate research analysis of the system to be used, uses the Unified Modeling Language (UML) with the modeling used is the Waterfall model, which describes the flow of the existing system that will be developed